2020
DOI: 10.1096/fj.202000408rr
|View full text |Cite
|
Sign up to set email alerts
|

Systemic deficiency of mouse arachidonate 15‐lipoxygenase induces defective erythropoiesis and transgenic expression of the human enzyme rescues this phenotype

Abstract: Oxidative stress, 1 which has been implicated in the pathogenesis of inflammatory, hyperproliferative, and neurodegenerative diseases, 2-4 is defined as an imbalance of the cellular redox equilibrium. At low concentrations, reactive oxygen species (ROS) function as second messengers 5 and are essential for proper cell function. In contrast, at higher levels ROS induce cellular malfunction and even cell death, such as apoptosis and/or necroptosis. 6,7 Usually, the intracellular redox homeostasis is well balance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…Indeed, 15-lipoxygenase (LOX), which directly oxidizes phosphatidylethanolamines to generate lipid hydroperoxides, is highly expressed in reticulocytes [ 48 , 49 ]. Whereas an early work found that erythrocyte and reticulocyte count were normal in 12/15-LOX knockout mice [ 50 ], a recent study revealed that the blood of 15-LOX -/- mice involved an increased proportion of structurally modified erythrocytes, although the structural and functional differences between wild-type and 15-LOX -/- erythrocytes are not very profound [ 51 ]. Erythropoietin reportedly affects enucleation negatively in association with cellular ROS [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, 15-lipoxygenase (LOX), which directly oxidizes phosphatidylethanolamines to generate lipid hydroperoxides, is highly expressed in reticulocytes [ 48 , 49 ]. Whereas an early work found that erythrocyte and reticulocyte count were normal in 12/15-LOX knockout mice [ 50 ], a recent study revealed that the blood of 15-LOX -/- mice involved an increased proportion of structurally modified erythrocytes, although the structural and functional differences between wild-type and 15-LOX -/- erythrocytes are not very profound [ 51 ]. Erythropoietin reportedly affects enucleation negatively in association with cellular ROS [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Osmotic resistance of erythrocytes —To assess the resistance of the red blood cells for osmotic stress, we followed the experimental protocol described before [ 25 ]. For this purpose, 2 μL of blood was diluted in 200 μL phosphate buffer (pH 7.4) containing NaCl at different concentrations (0–0.85%) and the cells were incubated for 30 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…With respect to therapeutic targeting, several inhibitors are at the developmental stages for specific targeting of 12-LOXs [ 146 ]. It is intriguing that in mouse models, depletion or inactivation of 12-LOX prevents major disease development and/or progression, though it will be important to determine if there are deleterious global effects of inactivation of the 12-LOXs, as the Alox15 null mice show hematopoietic defects leading to a myeloproliferative disorder as well as defective erythropoiesis [ 147 , 148 ]. Therefore, it is critical to follow these animal models for extended periods to ensure that there are no long-term adverse effects of 12-LOX inhibition.…”
Section: Discussionmentioning
confidence: 99%